"Riders on the storm": The Uncertainty Perception Indicator (UPI) in Q1 2021 - Henrik Müller; Jonas Rieger; Nico Hornig (TU Dortmund University, Dortmund Center for Data-based Media Analysis (DoCMA), 2021)
In this paper we update our Uncertainty Perception Indicator (UPI) with data from the first quarter of 2021. UPI values have declined in recent quarters. At first glance this might come as a surprise, with the third Corona wave having less of an impact than the first one, even though the former was several magnitudes bigger than the latter in Germany. This result underscores the difference between perception and actual impact: a shock hits the hardest when it first occurs because by then its nature is still unknown. As shown in previous versions of the UPI, uncertainty has mainly been fed by the political sphere since the 2010s. Towards the end of our observation period, however, uncertainty from the international and European political spheres is declining, while German domestic politics is on the rise. The end of Angela Merkel's chancellorship marks the end of a long period of relative political stability. Without her in the race the outcome of German federal elections in September is hardly predictable. Whatever coalition may succeed, it is likely that any future government will engineer a shift in (economic) policy. The potential strength of this "election uncertainty effect" is evident in our data. An update of our Fear Gauge shows profound shift in public discourse in Germany. With the pandemic in retreat for now, climate change and the question to what extent policies should follow science (whether on pandemics or global warming) are taking center stage in Germany. Looking ahead, we expect UPI values to rise again as the federal elections loom and the economic and political consequences of the pandemic (e. g. higher debt levels) become apparent. Uncertainty shocks tend to come in waves. Given the severity of the Corona pandemic, a host of difficulties - ranging from unexpected inflation to debt crises to geostrategic tensions - are possibly in the making.
hdl:2003/40300
Keywords: 330; Uncertainty; Narratives; Latent Dirichlet Allocation; Business Cycles; Covid-19; Text Mining; Computational Methods; Climate Change